The Use of Brown - Levinson’s Politeness Strategies As A Realization of Sociocultural Competence Among Adult Learners of Elti Surakarta - Gunaningtyas, Martha Tanjung; Wuli Fitriati, Sri (Universitas Negeri Semarang, 2021)
This study focuses on analyzing the use of Brown and Levinson's politeness strategies to reflect sociocultural competence among adult learners. English is an international language in international communication to talk with people of different age, gender, status, etc. Besides, politeness strategies can reflect somebody's sociocultural competence when he/she talks to others. At the beginning of this study, preliminary research showed that English was used as a language tool in the class for adult students in conversation classes. The adult students came from different backgrounds including job, age, gender, status, culture, existence, and experience. Some of them had been abroad and communicated with the English native speaker directly. A proficiency test was used at the beginning of the research. It was continued by a sound recorder, video recorder, DCT, and interview to get the data. The findings reveal the more prominent use in bald on record and positive politeness strategies. Those strategies, based on the theory of Brown and Levinson and Celce Murcia, showed there was a close relationship between the speakers. The rest of the strategies showed that there was a distance between the speakers. In conclusion, politeness strategies were in students' interactions to reflect their sociocultural competence. The suggestion focuses on giving practices to students to increase their experiences in implementing politeness strategies.